Pemberdayaan Literasi Digital Siswa melalui Kegiatan Lokakarya Kolaboratif Disarpus Karanganyar - Kurniawan, Wakhid; Romadloni, Nova Tri; Bintang, Rauhulloh Ayatulloh Khomeini Noor; Ardiansyah, Muhammad (Cahaya Pengabdian, 2025)
The rapid development of the digital era demands that the younger generation possess strong digital literacy skills. Digital literacy is not merely the ability to operate digital devices but also involves understanding ethics, security, and the capacity to critically evaluate information. This community service activity aimed to empower high school students in understanding and applying digital literacy through a workshop organized by the Department of Archives and Library (Disarpus) of Karanganyar Regency, in collaboration with lecturers from the Informatics Department of Universitas Muhammadiyah Karanganyar (UMUKA). The workshop was designed using a participatory approach and covered four pillars of digital literacy: hardware, software, digital ethics, and cybersecurity. Key topics included the dangers of cyberbullying, hoaxes, phishing, and best practices for protecting personal data, including the introduction of two-factor authentication (2FA) and Single Sign-On (SSO) technology. The activities included simulations, quizzes, and interactive discussions to enhance student engagement. The results showed a significant improvement in students’ understanding and awareness of the importance of being wise and safe in digital spaces. This program serves as an effective collaborative model between government institutions and higher education in enhancing students’ digital competencies. It is expected that similar initiatives can be replicated in other regions as a contribution to strengthening national digital literacy resilience.